Relationship between anaerobic alactic power and body composition in cadet wrestlers - Torres, Y. L. (International Journal of Wrestling Science, 2013)
PURPOSE: This study determined the relationship between Anaerobic Alactic Power (AAP) and Body Composition (BC) in cadet`s wrestlers. METHODS: Ten subjects of Greco Roman and Freestyle wrestling (16.62 + 0.53 years old) participated. To evaluate the strength/power - anaerobic alactic - (AAP) was estimated using the standard test developed by Bosco, using a platform contact Ergo Jump Bosco System. The protocol used for the assessment of body composition and muscle mass and area were the standards set by the International Society for the Advancement of Kinanthropometry (ISAK). The data analysis was performed using statistical software (SPSS) version 17.0. RESULTS: there was a significant correlation (positive) between the Countermovement Jump AAP and Medium Thigh Muscular Area (MTMA) (0.777**, P <0.01), Abalakov Jump AAP with the Skeletal Muscle Mass Percentage (% SMM) (0.632*, p <0.05), Arm Muscular Area (AMA) (0.866**, P <0.01) and with the Medium Thigh Muscular Area (0.929**, P <0.01) and Anaerobic Alactic Power Squat Jump of Arms (SJA) with % SMM (0.806**, p <0,01). CONCLUSIONS: It was found that the AAP and BC represent a critical role in the performance and success in the wrestling. There is a significant relationship between muscle mass and power levels generated by these subjects, therefore, increasing the SMM, or cross-sectional area of the muscles contribute to a higher level of anaerobic power output and better performance on tests strength/power. This information can help the coach to make adjustments that will allow a more specific schedule of training for their athletes, and lead to greater success.